2014
DOI: 10.1016/j.crohns.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Health determining concepts important to people with Crohn's disease and their coverage by patient-reported outcomes of health and wellbeing

Abstract: Background and aimsBusy clinical settings often restrict the possibility to focus on concepts that determine health in a positive way, commonly assessed by using patient-reported outcomes (PROs). We aimed to explore which determinants of health (DHs) are important to people with Crohn's disease (CD), to understand possible gender differences and to analyze whether these DHs are covered by PROs used in CD.MethodsTwo systematic literature reviews were done to identify relevant DHs and clinically relevant PROs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…The relationship between occupational balance and health has also been shown empirically. Participants in qualitative studies have described occupational balance as related to health and well-being (2)(3)(4)(5) and occupational balance has been recognized as a health determinant (6). Results of quantitative studies over the years have also supported the relationship with subjective health/ well-being.…”
Section: Introductionmentioning
confidence: 96%
“…The relationship between occupational balance and health has also been shown empirically. Participants in qualitative studies have described occupational balance as related to health and well-being (2)(3)(4)(5) and occupational balance has been recognized as a health determinant (6). Results of quantitative studies over the years have also supported the relationship with subjective health/ well-being.…”
Section: Introductionmentioning
confidence: 96%
“…Less is known about the role of such qualities for improving adjustment in IBD as empirical research on the psychological determinants of quality of life in IBD is scarce (van der Have et al, 2014). However, a qualitative narrative biographical study found that patient reports of optimism about living with the disease, and appreciation of help from others, were concepts that mapped on to better health and well-being outcomes (Dür et al, 2014). It is therefore likely that certain positive traits may also be beneficial for adjustment to IBD.…”
Section: Introductionmentioning
confidence: 99%
“…However, these have focused on a wide range of different outcomes. For example, Burkhalter et al 4 explored patients' clinical needs, Norton et al 5 compared experiences of patients receiving adalimumab with a group of biologic naïve patients and Dür et al 6 focused on what they termed the determinants of health. The overall focus of these studies was on how patients dealt with the burdens of symptoms and associated limitations in functioning resulting from CD.…”
Section: Introductionmentioning
confidence: 99%
“…Several stated that CD affects QoL,4 6 11 but none of the studies had assessed that outcome 12–15. Where they had used outcome measures, these were standardised measures of health-related quality of life (HRQL), such as the IBDQ 16.…”
Section: Introductionmentioning
confidence: 99%